Халық педагогикасында жасларға астрономиялық билим бериў мазмуны ҳәм оның турмыслық әҳмийети - Алеуов, У; Бекимбетова, А (SCIENCE and SOCIETY, 2016)
The article is devoted tо the study of the youth‘s astronomical knowledge in folk Pedagogy. The life on the earth and people‘s life are connected
Keywords: national Pedagogics; mental education; astronomic knowledge; the sun; the moon; movement of stars